P107 UK speech and language therapy (SLT) diagnostic and therapy services for inducible laryngeal obstruction. (11th November 2022) - Percy, S; Ludlow, SF; Tidmarsh, B; Fowler, SJ
Abstract : Introduction: Inducible laryngeal obstruction (ILO) is defined as an inappropriate laryngeal closure causing difficulty breathing. Speech and language therapy (SLT) is the cornerstone of treatment. This survey aimed to gain insight into ILO services within the UK and its treatment and management. Method: The 24-question online survey was completed by 43 speech and language therapists across the UK. Results: All participants had heard of the term 'ILO' and were practicing in a range of adult services; ENT (n=40), respiratory (n=25), head and neck cancer (n=14), acute (n=9), neurology (n=5), gastroenterology (n=7), allergy (n=5), critical care (n=4), rehabilitation (n=7), community (n=12) and other (n=4). 31 participants (74%) were involved in ILO diagnosis, 36 (83%) in treatment, 34 (79%) worked within a multi-disciplinary team (MDT) which included respiratory physicians (n=26), ENT consultants (n=34), SLT (n=36), physiotherapists (n=21), psychologists (n=10), clinical nurse specialists (n=16), dieticians (n=12), gastroenterologist (n=10), nurse (n=2). 15 (36%) have access to local MDT meetings, 5 (12%) regional MDT meetings, 39 (90%) to laryngoscopy and 14 (33%) to provocation laryngoscopy. Laryngoscopy (± provocation) was completed by ENT (n=19), SLT (n=11), respiratory physician (n=3) or other (n=6). Participants reported patients having a range of co-morbidities including asthma (n=40), breathing pattern disorder (n=35), reflux (n=39), nasal disease (n=25), bronchiectasis (n=22), chronic cough (n=37) and other (n=15) and had access to a range of diagnostic testing. Therapy was provided either face to face (n=17), virtually (n=2), both (n=17) or neither (n=5). Most therapy was provided one-to-one (94%) with one SLT providing group therapy. The wait time for diagnosis ranged from less than 3 months (n=9), 3–6 months (n=16), 7–12 months (n=7) and greater than 12 months (n=2). The wait time for therapy ranged from less than 3 months (n=19), 3–6 months (n=14), 7–12 months (n=2). Barriers to treatment and diagnosis are shown in figure 1 . Conclusions: Participants felt the greatest barriers to service development were lack of funding, training, and expertise. We hope this survey will identify the need for further service provision and aim for more streamlined services, reducing inequalities depending on geographical location.